High post-operative pain scores despite multimodal analgesia in ambulatory anorectal surgery: a prospective cohort study. Issue 4 (4th July 2019) - Ceulemans, Aline; De Looze, Danny; Van de putte, Dirk; Stiers, Eline; Coppens, Marc
Abstract: Background: Ambulatory surgery for anorectal procedures has become widely accepted. Recent reviews recommend a multimodal approach to pain management. However, these recommendations are largely based on single intervention studies. Our goal was to evaluate post-operative pain in patients receiving a multimodal analgesic regimen. Methods: All patients undergoing an ambulatory anorectal procedure between December 2015 and September 2016 received a pain diary. Mean pain throughout the day and pain during defecation where recorded on day 0–14 and day 21 postoperatively using a numeric rating scale-11. Use of oral analgesics was also recorded. Results: Forty-two patients completed the pain diary. The use of local anesthetic infiltration did not result in a significant difference in pain scores in this study. Patients who received written information on postoperative pain management and hygienic measures had higher intake of oral analgesics. Despite receiving multimodal analgesic treatment, patients undergoing surgery for hemorrhoids or anal fissures reported pain scores ≥4 and used analgesics longer. Conclusion: A multimodal analgesic approach consisting of local anesthetic infiltration, multiple oral analgesics and written information seems to be insufficient for certain patient groups after ambulatory anorectal surgery. Especially patients undergoing surgery for hemorrhoids or an anal fissure should receive adequate analgesia. Pain during defecation is problematic and finding a solution for this problem remains challenging. Further research into the combined use of different analgesic modalities is recommended.